Preparation of bioclimatograph for haemonchosis and trichostrongylosis in goats of subtropical high humid zone of Sikkim - PAL, PAPRI; CHATLOD, L R; AVASTHE, R K (The Indian Journal of Animal Sciences, 2017)
Based on a systematic epidemiological study, bioclimatographs were prepared for Haemonchus and Trichostrongylus spp. infecting goats of subtropical high humid zone of Sikkim, India. Three meteorological parameters i.e., maximum and minimum temperature, average relative humidity and total rainfall were recorded for each month from April 2012 to March 2013 and correlated with faecal egg count, faecal larval count and pasture larval count of grazing area under investigation. Bioclimatographs were prepared against different meteorological parameters and the predicted values were correlated with actual field study. The findings in goats revealed higher rate of infection of Haemonchus and Trichostrongylus spp. from July to October and September to early March and higher intensity from June to October and November to February, respectively. The higher incidence of infection of larval stages on pasture was observed from June to October for Haemonchus spp.The prediction or forecasting of Haemonchus spp. and Trichostrongylus spp. infection in goats of this agroclimatic region as per bioclimatographs revealed a prediction for development and survival of eggs and larvae of Haemonchus spp. infection from July to October and for Trichostrongylus spp. from September to February. Bioclimatographs revealed that maximum temperature (Tmax.) v/s total rainfall (TRF) and Tmax. v/s relative humidity (RH) gave better prediction for Haemonchus spp, while for Trichostrongylus spp. it was minimum temperature (Tmin.) v/s RH.